Optimization of Therapy in Patients with Epilepsy and Psychiatric Comorbidities: Key Points - Pisani, Francesco; Rosa Pisani, Laura; Barbieri, Maria A.; de Leon, Jose; Spina, Edoardo (Current Neuropharmacology, 2023)
Psychiatric disorder comorbidity in patients with epilepsy (PWE) is very frequent with a mean percentage prevalence of up to 50% and even higher. Such a high frequency suggests that epilepsy and psychiatric disorders might share common pathological pathways. Various aspects contribute in making the matter very complex from a therapeutic point of view. Some antiseizure medications (ASMs), namely valproic acid, carbamazepine, and lamotrigine, have mood-stabilising effects and are routinely used for the treatment of bipolar disorder in patients who do not have epilepsy. Pregabalin and, to a lesser extent, gabapentin, exerts anxiolytic effects. However, several ASMs, in particular levetiracetam, topiramate, and perampanel, may contribute to psychiatric disorders, including depression, aggressive behaviour, and even psychosis. If these ASMs are prescribed, the patient should be monitored closely. A careful selection should be made also with psychotropic drugs. Although most of these can be safely used at therapeutic doses, bupropion, some tricyclic antidepressants, maprotiline, and clozapine may alter seizure threshold and facilitate epileptic seizures. Interactions between ASMs and psychotropic medication may make it difficult to predict individual response. Pharmacokinetic interactions can be assessed with drug monitoring and are consequently much better documented than pharmacodynamic interactions. Another aspect that needs a careful evaluation is patient adherence to treatment. Prevalence of non-adherence in PWE and psychiatric comorbidities is reported to reach values even higher than 70%. A careful evaluation of all these aspects contributes in optimizing therapy with a positive impact on seizure control, psychiatric wellbeing, and quality of life.
Keywords: adherence